Assessment of Organic Farming Practices and Their Impact on Soil Health and Ecosystem Services: A Review - , Ravindra Pratap Singh Jetawat; , Manoj Nazir; , Rashmi Mohapatra; , Khushboo Jyotsna Baxla; , Harshvardhan Bhagwan Gokhale; , Saransh Kumar Gautam; , Vimal Kumar (Archives of Current Research International, 2025)
Organic farming is increasingly recognized as a sustainable agricultural approach that enhances soil health, biodiversity, and ecosystem services while mitigating environmental impacts. The principles of organic agriculture are based on four key pillars: health, ecology, fairness, and care. This review examines the effects of organic farming practices on soil health indicators, including physical, chemical, and biological properties, and evaluates their contributions to various ecosystem services. Studies show that organic systems promote higher soil organic matter (SOM) content, improved aggregate stability, and greater microbial diversity, resulting in enhanced nutrient cycling, carbon sequestration, and soil fertility. Compared to conventional systems, organic farming demonstrates a 20–40% increase in microbial biomass and a 15–25% increase in SOM, contributing to improved soil structure and resilience. Organic farming also supports biodiversity conservation, with 30–50% more species of plants, insects, and soil microorganisms observed in organic systems. Despite these benefits, yield gaps of approximately 20–25% persist for specific crops, particularly cereals. Organic farming helps achieve sustainability goals by contributing to climate mitigation through enhanced carbon sequestration, reduced greenhouse gas emissions, and improved soil health. Again, biodiversity conservation is a critical component of organic farming's contribution to sustainability. Economic sustainability is another essential aspect of organic farming's contribution to sustainability goals. Economic profitability remains promising, with organic systems achieving 20–30% higher profitability due to premium prices and reduced input costs. Challenges related to productivity, market access, and scalability continue to limit the broader adoption of organic practices. Future research should focus on improving organic inputs, enhancing nutrient cycling, and developing ecosystem service assessments. Improving the economic viability of organic farming is essential for promoting its widespread adoption. Effective policies are essential for encouraging the adoption of organic farming practices. Government policies that provide subsidies, technical assistance, and research funding can enhance the scalability of organic systems. Addressing economic and policy barriers is essential for promoting widespread adoption. The findings suggest that organic farming can significantly contribute to global sustainability goals related to food security, climate change mitigation, and environmental conservation.